The environment as a challenge for governmental responsibility: The case of the European Water Framework Directive - Thomas Petersen; Bernd Klauer; Reiner Manstetten (Helmholtz-Zentrum für Umweltforschung (UFZ), 2008)
The European Water Framework Directive is shaping a new conception of integrative water protection. In this article, the consequences of the Water Framework Directive in respect to national environmental policy will be discussed in referring to the notion of responsibility which is a central concept of political philosophy and theory. It will be shown that the new conception of integrative water protection entails a fundamental change in European water protection policy and also environmental policy at all. It implies that environmental policy has not only to prevent environmental damage but in particular has to warrant a good status of the environment, such that it must maintain a good status of water or even achieve it if this status does not exist. Achieving and maintaining a good status of the environment is, however, an encompassing task. Thereby, state power and will eventually be overexerted. The threat of such overexertion has to be kept in mind in discussing the perspective of the so called New Environmental Governance. It will be pointed out that the New Environmental Governance is not primarily a form of some sort of democratic participation but rather designed to improve state power in environmental politics.
Keywords: 330; Environmental politics; European Water Framework Directive; Responsibility; Environmental Governance; EU-Umweltpolitik; Wasserrecht; EU-Recht; Wasserpolitik; Verantwortung; EU-Staaten